(untitled) (Revista Contexto & Educação, 2023)
The pandemic caused by Covid-19, and the consequent Emergency Remote Teaching implemented, accelerated the process of discussion about the potential of Blended Learning and Active Methodologies, with a view to transforming the teaching-learning methods hitherto established and the search for answers for the following questions: "How to rescue students’ interest in learning?" and “How to guarantee learning that actually provides the formation of reflective citizens and protagonists of their learning?”. It is in this context that we propose to carry out this Systematic Mapping (MS), with the aim of identifying primary studies, developed nationally and internationally, which investigate how Blended Learning and Active Methodologies are being made viable in the educational context, both in the basic and higher education, investigating the impact on the teaching-learning process. The analysis allowed us to identify that Blended Learning and Active Methodologies impact on different dimensions in the teaching-learning process, related to intrinsic and extrinsic aspects, presenting themselves as a possibility to answer the questions initially listed. This work provides the academic and scientific community with a comprehensive survey of research and experience reports, pointing out the existing gaps and directing new efforts in studies and educational practices.